Multiphysics modelling of MICP grouting for drawdown control and curtain stability in confined aquifers with partially penetrating barriers during deep excavation - Sharif Nyanzi Alidekyi; Jianxiu Wang; Weiqiang Pan; Muhammad Arslan Ahmad; Yanxia Long; Naveed Sarwar Abbasi; Aamir Khan Mastoi (Computers and Geotechnics, 2027)

CRIP1 knockdown enhances glycolytic dependence and increases sensitivity to 2-Deoxy-D-Glucose in acute myeloid leukemia - Muhammad Asif Zeb; Faryal Mehwish Awan; Aamir Ali Khan; Sadiq Noor Khan (Molecular Biology Reports, 2026)

Protective efficacy of Allium cepa, Withania somnifera and polyflavonoid quercetin against Naja naja envenoming in mice: An integrated in vitro and in vivo study - Ayesha Muzamil; Hafiz Muhammad Tahir; Aamir Ali (Toxicon, 2026)

Exogenous dopamine alleviates chilling injury of sapodilla (Manilkara zapota) fruit by modulating reactive oxygen species and ascorbate-glutathione cycle activities - Sajid Ali; Syed Muhammad Kashan Haider; Safina Naz; Hafiz Umer Javed; Aamir Nawaz; Shaghef Ejaz; Muhammad Shahzad Saleem (Postharvest Biology and Technology, 2026)

Bacteriophage therapy for antimicrobial-resistant, biofilm‑associated diabetic foot infection: delivery routes, phage antibiotic synergy, and practical wound‑care integration - Muhammad Irbaz; Zunaira Hamood; Summayah Shahid; Afra Ghufran; Aamir Ajmal; Iqra Rafiq (Archives of Microbiology, 2026)

Retraction Note: Integrating physiological and molecular insights in cotton under cold stress conditions - Aamir Ali Abro; Muhammad Qasim; Mubashir Abbas; Noor Muhammad; Ijaz Ali; Shiguftah Khalid; Junaid Ahmed; Muhammad Waqas; Sezai Ercisli; Rashid Iqbal; Fang Liu (Genetic Resources and Crop Evolution, 2026)

Dual upcycling of waste PET into both the porous support and the Al-MOF filler of thin film nanocomposite nanofiltration membranes - Aroosa Nehal; Aamir Razaq; Asim Laeeq Khan; Muhammad Yasin; Gianluca Viscusi; Giuliana Gorrasi; Mazhar Amjad Gilani; Beenish Shazadi (Journal of Water Process Engineering, 2026)

Biomass-derived MOF@cellulose composites for sustainable separation and energy applications - Sadaf Zulfiqar; Changjiang Liu; Zunaira Zulfiqar; Aamir Razaq; Khair Muhammad; Tianzhen Zhu; Yang Wang (Journal of Environmental Chemical Engineering, 2026)

Investigational Studies of Mn/Ag/Graphene@PANI Quaternary Composite for Ni(II) Removal Efficiency - Muhammad Saleem; Aamir Rasheed; Aneeqa Surkhab; Mahnoor Shireen; Rana Hamza Zafar (Water, Air, & Soil Pollution, 2026)

Retraction Note: Impact of elevated temperatures on the genetic and morpho-physiological traits of cotton genotypes cultivation - Aamir Ali Abro; Muhammad Qasim; Muhammad Usama Younas; Ijaz Ali; Mubashir Abbas; Noor Muhammad; Shiguftah Khalid; Junaid Ahmed; Umbreen Bibi; Muhammad Waqas; Sezai Ercisli; Fahad Al-Asmari; et al. (Genetic Resources and Crop Evolution, 2026)

Elevated DNA 5-hydroxymethylation promotes chondrocyte differentiation via TET-mediated epigenetic downregulation of hTERT in human mesenchymal stem cells - Naeem Ullah; Fazal Jalil; Muhammad Jaseem Khan; Muhammad Umair; Waseem Iqbal; Aamir Ali Khan (Histochemistry and Cell Biology, 2026)

In silico pharmacological evaluation of a multi-epitope vaccine candidate targeting the G1 and G2 glycoproteins of Oropouche virus via TLR3 interaction - Khadija Khawar; Komal Imran; Muhammad Aamir Sharif; Muhammad Naveed; Nantenaina Tombozara; Maha A. Alwaili; ‏Mariam A. Alkhateeb; Seham O. Alsulami (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Optogenetic Pacemaker Cells for Biological Cardiac Rhythm Management in Sick Sinus Syndrome - Versha Devi; Syeda Aliza Aamir; Syed Abdullah Shah; Muhammad Dawood Ghaffar; Muhammad Talha; Muneeb Saifullah (Cell Biochemistry and Biophysics, 2026)

Cytotoxic and computational profiling of 2-mercaptobenzimidazole Mannich derivatives: structure activity relationship and carbonic anhydrase binding assessment - Muhammad Naeem; Arooj Mohsin Alvi; Muhammad Mehmmod Moin Ul Haq; Najia Shabbir; Shumaila Mehdi; Areen Khalid; Saqib Khan; Hafiz Muhammad Ahmad; Najm Ul Hassan Khan; Muhammad Nouman Arif; Hafiz Aamir Ali Kharl (Inflammopharmacology, 2026)

Non-destructive classification of type 2 diabetic teeth using LIBS-derived elemental biomarkers and machine learning - Muhammad Mustafa Dastageer; Khurram Siraj; Giorgio Saverio Senesi; Muhammad Aamir Israr; S.U. Haq (Analytica Chimica Acta, 2026)

From reagents to feedstocks: reprogramming heteroatom-containing molecules in modern organic synthesis - Jixiang Ni; Mohd. Aamir Bin Riyaz; Zhenyu An; Yang Lu; Sajid Muhammad; Yanguo Li; Ning Xi; Yufen Zhao (Molecular Diversity, 2026)

Unraveling Luteolin’s Modulatory Effects on α-Synuclein Aggregation: A Combined Biophysical, Computational, and C. elegans Approach - Syed Moasfar Ali; Md Nadir Hassan; Nida Zaidi; Muhammad Uzair Ashraf; Mahmood Akbar; Aamir Nazir; Rizwan Hasan Khan (Cell Biochemistry and Biophysics, 2026)

Nitrogen atom insertion and related skeletal editing strategies in aromatic heterocycles for drug discovery (2015–2025) - Jixiang Ni; Mohd. Aamir Bin Riyaz; Zhenyu An; Yang Lu; Sajid Muhammad; Chao Zhang; Ning Xi; Yufen zhao (Molecular Diversity, 2026)

Advancements in Wheat Rust Resistance through Molecular and Field-Based Approaches - Muhammad Waheed Riaz; Dehua Wang; Shams ur Rehman; Yufeng Zhang; Faheem Tariq; Alam Sher; Shabbir Hussain; Muhammad Aamir Manzoor; Abdul Raziq; Zhiying Deng (Journal of Soil Science and Plant Nutrition, 2026)

Vinca Extract Infused Silk Fibroin Hydrogel for Treatment of Artificially Induced Diabetic Foot Ulcer in Murine Model - Ayesha Afzal; Hafiz Muhammad Tahir; Aamir Ali; Ayesha Muzamil; Navera Afzal; Sania Faiz; Farwa Shafeeq; Sidra Arshad; Rida Mahnoor (Cell Biochemistry and Biophysics, 2026)

Thermal analysis of nonsymmetric stress tensor on a partially ionized viscoelastic non-Newtonian fluid flow with convective boundary conditions (A numerical study) - Muhammad Naveed Khan; Aamir Abbas Khan; Haifaa F. Alrihieli; Walid Abdelfattah; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2026)

Strigolactone-mediated regulation of chromium uptake, redox homeostasis, and photosynthetic carbon metabolism during Cr (VI) stress tolerance in Capsicum annuum L. - Kaiser Iqbal Wani; Huazheng Shao; Yingsai Li; Muhammad Aamir Manzoor; Huizhen Fu; Xu Lu; Shanhan Cheng; Javaria Tabusam; Tariq Aftab; Zhiwei Wang (Plant Cell Reports, 2026)

Paleocene stratigraphic framework and sedimentary architecture in the Sub-Himalayan Fold and Thrust Belt of Muzaffarabad, Pakistan: Depositional environment, Biotas, Paleogeographic and Economic Significance - Syed Kamran Ali; Arslan Sajjad; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Aamir Asghar; Aijaz Ali Halepoto; Evangelia Besiou; Assimina Antonarakou (Journal of Sedimentary Environments, 2026)

Integrating crowdsourced geospatial intelligence and urban morphology for urban waterlogging risk mapping in Karachi, Pakistan - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Yinghai Li; Chengshuai Liu; Junaid Abdul Wahid; Jiali Guo; Xiaotao Shi; Gul-e-Zehra Soomro (Climatic Change, 2026)

Bioprocess parameter screening and condition selection for single-cell protein production using yeast co-culture and agro-food waste substrates - Zukhruf Asim; Hafiz Muhammad Aamir Shahzad; Khalid Ouararhni; Fares Almomani; Kashif Rasool (Process Safety and Environmental Protection, 2026)

A novel spatiotemporal and machine learning framework for sustainable groundwater monitoring and management - Sheraz Maqbool; Muhammad Imran Khan; Aamir Raza; Mumtaz Ali; Naeem Saddique; Qaisar Saddique (Groundwater for Sustainable Development, 2026)

Amine-appended bimetallic MOF-74 for highly selective and energy-efficient CO₂ capture under vacuum swing adsorption - Rodynah A. Alabdulhadi; Shabnam Khan; Md Delowar Hossain; Aamir Hanif; Mohammed Ahmed Sanhoob; Mohd Yusuf Khan; Mosim Ansari; Aasif Khan; Muhammad Usman; Saleh AlMansour; Aasif Helal (Chemical Engineering Journal, 2026)

Evolutionary insight and characterization of WOX genes in callus development and differentiation of Peucedanum praeruptorum - Cheng Song; Haoyu Pan; Muhammad Arif; Haiyu Wang; Yunpeng Cao; Bangxing Han; Muhammad Aamir Manzoor (Planta, 2026)

The first complete genome sequence of a highly pathogenic fowl adenovirus serotype 4 isolate from an infected chicken in Pakistan reveals the absence of a natural large genomic deletion - Salman Ahmad; Syeda Fakhra Waheed; Itra Ayoub; Ayesha Siddiqua; Soban Tufail; Sofia Irfan; Raheem Ullah; Muhammad Salahuddin Shah; Mazhar Iqbal; Moazur Rahman; Aamir Shehzad (Archives of Virology, 2026)

Surveillance of citrus canker: a threat to Pakistani citrus industry-status and distribution of citrus canker in major citrus growing regions of Pakistan - Safi Ullah; Zia ur Rehman; Muhammad Tayyab; Aamir Iqbal; Abdullah Jalal; Jinbiao Ma; Muhammad Awais; Sajid Ali (Journal of Plant Pathology, 2026)

Evaluation of immunogenicity and protective efficacy of Salmonella Gallinarum knockout purB mutant strain in chicken - Muhammad Umer Farooq; Masham Mukhtar; Muhammad Suleman; Minahil Ashraf; Muhammad Abu Bakr Shabbir; Muhammad Hassan Mushtaq; Umar Bin Zahoor; Shakil Abbas; Aamir Ghafoor (Veterinary Research Communications, 2026)

Combined application of 5-ALA and nitric oxide improves lead detoxification and antioxidant defense in barley - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Wael Elmenofy; Muhammad Aamir Manzoor; Rashid Iqbal (Biodegradation, 2026)

Optimization of Tissue Culture Media for Microtuber Development Incorporating Sugars and Zinc Nanoparticles - Muzammil Anwar Khan; Naima Huma Naveed; Aamir Ali; Muhammad Adeel; Aima Iram Batool; Tahir Shahzad; Muhammad Rizwan Khan; Salman Majeed (American Journal of Potato Research, 2026)

Bacteriophage-Based Vaccine Platform for Next Generation Vaccine Development Against Bovine Tuberculosis and Other Pulmonary Diseases of Animals - Shahzar Khan; Nadia Ilyas; Fida Ullah Khan; Aneela Nawaz; Mohammed Raashid; Muhammad Ismail Khan; Momina Aamir; Aamer Ali Shah; Malik Badshah; Brekhna Alam; Samiullah Khan (International Journal of Peptide Research and Therapeutics, 2026)

Electroactive PVDF/Ti3C2Tx MXene functionalized nanofiber mats with high surface potential for high-efficiency indoor & outdoor submicron PM(0.3-2)μm filtration - Ashish Kakoria; Mirza Muhammad Zaid; Aamir Iqbal; Mahsa Moradi; Lina Zheng; Guang Xu (Environmental Pollution, 2026)

Investigation of heat and mass transfer in an electromagnetically driven ionized tri-hybrid nanofluids flow over a convectively heated cylinder - Muhammad Naveed Khan; Shafiq Ahmad; Aamir Abbas Khan; Mounirah Areshi; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2026)

Synergistic yeast co-culture and pretreatment optimization for enhanced single cell protein production from agro-waste - Zukhruf Asim; Hafiz Muhammad Aamir Shahzad; Khaled A. Mahmoud; Fares Almomani; Kashif Rasool (Biomass and Bioenergy, 2026)

Nano-silicon-induced modulation of heavy metal metabolism in plants: pathways to climate-resilient phytoremediation - Muhammad Nazim; Abida Hussain; Aamir Nawaz; Shazia Anjum; Muqarrab Ali; Xiangyi Li (Nanotechnology for Environmental Engineering, 2026)

Computationally guided synthesis and biological profiling of chalcones as antioxidant and anti-inflammatory activities - Hafiz Aamir Ali Kharl; Muhammad Naeem; Shakira Ghazanfar; Arifa Mehreen; Hasnain Haider; Sumel Ashique; Sabina Yasmin; Fatimah M. Al-Salem; Md Yousuf Ansari (Inflammopharmacology, 2026)

Nigella sativa L. (Black cumin) seeds impart protective effects against Staphylococcus aureus induced septic arthritis through the modulation of immune and inflammatory responses - Muhammad Aamir Shaheen; Adeel Sattar; Huma Rao; Amjad Riaz; Abdul Basit (Food Bioscience, 2026)

GeoFedNet: Federated learning for privacy-aware, robust, and generalizable seismic interpretation - Muhammad Saif ul Islam; Aamir Wali (Computers & Geosciences, 2026)

Anti-arthritic and anti-inflammatory effects of BMZD-2CPE in a CFA and carrageenan-induced animal model - Samiullah Wazir; Farah Abid; Aisha Mobashar; Arham Shabbir; Muhammad Awais; Humaira Nadeem; Hafiz Aamir Ali Kharl; Esmael M. Alyami; Amir Bouallegue; Norah Hamdi; Mohammed Bourhia; Abdullah R. Alanzi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Structural and computational analysis of monkeypox virus methyltransferase: dynamic inhibition mechanisms and their implications for antiviral design - Muhammad Waqas; Syed Ahsan Shahid; Muhammad Shahab; Yongkun Zhu; Aamir Fahira; Zunnan Huang (Molecular Diversity, 2026)

Synergistic efficacy of Azadirachta indica and biocontrol agents in mitigating Meloidogyne javanica infection in peach - Muhammad Saeed; Tariq Mukhtar; Raees Ahmed; Umair Mehmood; Muhammad Aamir Iqbal (Australasian Plant Pathology, 2026)

Magnoflorine and its structural diversity: mechanisms, and drug discovery opportunities a review - Muhammad Muzammil Nazir; Ghanva Mustafa; Saira Saeed; Warisha Ghaffar; Iqra Farzeen; Aamir Masood; Asma Ashraf (Molecular Diversity, 2026)

A comprehensive insight on the bioactive phytochemicals and pharmacological propensities of Ficus benghalensis L.: a reservoir for modern drug discovery - Sulaman Yaqub; Muhammad Islam; Hamid Saeed; Abrar Ahmad; Khurram Aamir; Rida Naeem; Meerab Tanveer (Phytochemistry Reviews, 2026)

Enhancing generalization in seismic image segmentation through multi-dataset integration and transfer learning - Muhammad Saif ul Islam; Aamir Wali (Journal of Earth System Science, 2025)

Bacteriophage-based vaccination platform for antigen discovery and development of next-generation vaccines - Shahzar Khan; Nadia Ilyas; Aneela Nawaz; Muhammad Ismail Khan; Momina Aamir; Nauman Ahmed Khalid; Aamer Ali Shah; Numan Saleh Zada; Ghulam Shabbir; Malik Badshah; Samiullah Khan (Next Research, 2025)

Influence of superabsorbent polymer and jute covering as internal and external curing techniques on the concrete compressive strength development: Experimental and comparative computational analysis - Umar Khurram Iqbal Khan; Hilal Khan; Atif Mehmood Khan; Hassan Khan; Muhammad Jibran Tariq; Hashim Khan; Muhammad Aamir Khan (Next Research, 2025)

Facile synthesis of novel MgO/NaCl nanosheets for extremely high Ni(II) adsorption from aqueous solutions: Experimental, mathematical, DFT and Box-Behnken design analysis - Khurram Shehzad; Aqdas Shehzad; Mukhtar Ahmad; Hongbo Ou; Suci Meng; Muhammad Aamir Aslam; Umer Farooq; Yan Wang; Min Chen; Yu Gan; Yuanguo Xu (Journal of Environmental Chemical Engineering, 2025)

Energy transport in ternary hybrid nanofluid with variable thermal conductivity under the combined effects of electroviscous, electric potential, and heat generation - Shafiq Ahmad; Aamir Abbas Khan; Muhammad Naveed Khan; Salah Knani; N. Ameer Ahammad; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2025)

Smart and Sustainable Microplastic Removal: Hybrid Systems, Bio-Inspired Technologies, Real-Time Sensing, and Policy Integration - Salman khan; Umme Kalsoom; Muhammad Kashif; Syed Aamir Hussain; Misbah Gul; Shohreh Azizi; Malik Maaza (Water, Air, & Soil Pollution, 2025)
The pervasive accumulation of microplastics in aquatic ecosystems has emerged as a critical global environmental challenge with profound implications for biodiversity, food safety, and human health. Conventional remediation approaches often fail to address microplastics' complex physiochemical diversity and resilience. In recent years, hybrid and bio-inspired technologies have emerged as promising alternatives for efficient microplastic remediation. This review critically examines the state-of-the-art hybrid systems comprising synergetic combinations of physical, chemical, and biological processes and bio-inspired approaches that mimic natural filtration, adhesion, and degradation mechanisms. Emphasis is placed on membrane-based hybrids, nature-mimicking adsorbents, and enzyme-functionalized materials and microrobots, as well as recent advances in smart monitoring systems and sensor technologies for real-time detection. Additionally, the review highlights the importance of integrated policies and technological synergies, stressing the need for harmonized regulatory frameworks and cross-sector collaboration to enable scalable and sustainable solutions. By integrating interdisciplinary insights, this work positions hybrid, bio-inspired and data-informed strategies at the forefront of sustainable solutions for microplastic remediation, paving the way toward cleaner ecosystems and circular plastic economies.

Variations in Wheat and Soil N Concentration by the Sole and Combined Foliar Application of NPK and Humic Acid Levels - Khadim Dawar; Shahid Ali; Ibad Ullah; Ishaq Ahmad Mian; Bushra Khan; Muhammad Tariq; Aamir Khan; Syed Sartaj Alam; Muhammad Mudasar Malik (Journal of Soil Science and Plant Nutrition, 2025)

Weighted ensemble transfer learning with EfficientNet: Advancing salt body segmentation in seismic imaging - Muhammad Saif ul Islam; Aamir Wali (Computational Geosciences, 2025)

Analyzing the double-chain deoxyribonucleic acid model: bifurcation, chaos, and sensitivity insights through advanced analytical techniques - Sadique Rehman; Aamir Farooq; H. W. A. Riaz; Kamran Ullah Khan; Majid Hussain Shah; Muhammad Ramzan (Theory in Biosciences, 2025)

Exploring nonstructural NS5B protein to design a multi-epitope-based vaccine against HCV: immuno-informatics approach - Nouman Ali; Adeeba Ali; Muhammad Sheraz Yousuf; Arsheen Rehman; Saad Muhammad Islam; Bilal Ilyas; Aamir Ali (In Silico Pharmacology, 2025)

Larvicidal Effects of Nanoliposomes Containing p-Cresol and Myristica fragrans Houtt. Essential Oil Against Aedes aegypti and Aedes albopictus Mosquitoes - Aamir Ali; Hafiz Muhammad Tahir; Muniba Tariq; Hooria Ashraf Khan; Ayesha Muzamil; Kiran Zainab; Asjid Ghaffar (Neotropical Entomology, 2025)

Predicting Wheat Grain Yield Through Morphometric Analysis of Seed Dimensions Using Computational Imaging Techniques - Mahnoor; Muhammad Jamil; Aamir Ali; Tauseef Anwar; Huma Qureshi; Muhammad Tahir Naseem; Gadah Albasher; Mohammad Javed Ansari (Plant Molecular Biology Reporter, 2025)

Comparative assessment of biochar and vermicompost on chromium bioavailability and stress alleviation in tomato (Solanum lycopersicum) - Jamaluddin Kabir; Muhammad Ansar Farooq; Shumaila Parvez; Aamir Alaud Din; Ghulam Abbas; Minggang Xu; Muhammad Mohsin Abrar (Journal of Soils and Sediments, 2025)

Survey and seasonal abundances of major insect pest species in the maize fields of Punjab, Pakistan - Naveed Akhtar; Hafiz Muhammad Tahir; Azizullah; Aamir Ali; Rabia Fajar; Ayesha Muzamil; Reham Fathy; Hend O. Mohamed; Dilawar Abbas (International Journal of Tropical Insect Science, 2025)

Transforming cities from traditional to sustainability: role of electric vehicles and solar photovoltaic energy in decarbonization - Noman Sahito; Muhammad Yousif Mangi; Muhammad Aamir Basheer; Farrukh Baig; Zulfiqar Ali Lashari; Saima Kalwar (Environment, Development and Sustainability, 2025)

Beyond Data, Towards Sustainability: a Sydney Case Study On Urban Digital Twins - Ammar Sohail; Bojie Shen; Muhammad Aamir Cheema; Mohammed Eunus Ali; Anwaar Ulhaq; Muhammad Ali Babar; Asama Qureshi (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2025)
As urban areas grapple with unprecedented challenges stemming from population growth and climate change, the emergence of urban digital twins offers a promising solution. This paper presents a case study focusing on Sydney’s urban digital twin, a virtual replica integrating diverse real-time and historical data, including weather, crime, emissions, and traffic. Through visualization and data analysis techniques, the study explores some applications of this digital twin in urban sustainability, such as spatial ranking of suburbs and automatic identification of correlations between variables. Additionally, the research delves into predictive modeling, employing machine learning to forecast traffic crash risks using environmental data, showcasing the potential for proactive interventions. The contributions of this work lie in the comprehensive exploration of a city-scale digital twin for sustainable urban planning, offering a multifaceted approach to data-driven decision-making

Machine learning-based screening and molecular simulations for discovering novel PARP-1 inhibitors targeting DNA repair mechanisms for breast cancer therapy - Muhammad Shahab; Muhammad Waqas; Aamir Fahira; Bharat Prasad Sharma; Haoke Zhang; Guojun Zheng; Zunnan Huang (Molecular Diversity, 2025)

Interactive impacts of heat stress and microplastics contamination on the growth and biochemical response of wheat (Triticum aestivum) and maize (Zea mays) plants - Muhammad Sajjad; Saraj Bahadur; Muhammad Aamir Farooq; Ming-Xun Ren (Ecotoxicology, 2025)

Building a high-resolution seismic impedance model via application of a novel grid conversion technique: implications for gas reservoirs - Tahir Azeem; Wang Yan Chun; Faisal Rehman; Muhammad Toqeer; Aamir Ali (Arabian Journal of Geosciences, 2025)

Unveiling the power of PavGID1s: the critical player in sweet cherry flower bud dormancy release - Xunju Liu; Li Wang; Muhammad Aamir Manzoor; Wanxia Sun; Yan Xu; Muhammad Salman Haider; Zhengxin Lv; Jiyuan Wang; Ruie Liu; Songtao Jiu; Caixi Zhang (Plant Molecular Biology, 2025)

Amendment of Tomato (Lycopersicon esculentum L.) Grown in Calcareous Soil with Spent Mushroom Substrate-derived Biochar: Improvement of Morphological, Biochemical, Qualitative Attributes, and Antioxidant Activities - Hasan Sardar; Muhammad Waqas; Aamir Nawaz; Safina Naz; Sajid Ali; Shaghef Ejaz; Riaz Ahmad; Ayman A. Ghfar; Saikh M. Wabaidur; Sami Abou Fayssal (Journal of Soil Science and Plant Nutrition, 2025)

Inheritance of Cell Membrane Stability and Yield Components Under Drought and Salinity Stress in Bread Wheat (Triticum aestivum L.) - Sameena Naqi; Aamir Hamid Khan; Rashid Mehmood Rana; Muhammad Imran Hamza; Marcin Kiedrzyński; Muhammad Naveed Tahir; Munir Ahmad; Shah Saud; Shah Hassan; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Urban cities heatwaves vulnerability and societal responses towards hazard zoning: Social media real-time based heatwave detection using deep learning - Shan-e-hyder Soomro; Muhammad Waseem Boota; Gul-e-Zehra Soomro; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Yinghai Li; Jiali Guo; Junaid Abdul Wahid (Sustainable Cities and Society, 2025)

Exploring the potential of a pH-sensitive hydrogel sponge: interpenetrating network of tragacanth and pectin for controlled delivery of levosulpiride - Muhammad Umer Ashraf; Muhammad Awais Iqbal; Kashif Barkat; Irfan Anjum; Muhammad Naveed Mushtaq; Rabia Gul; Muhammad Aamir; Samir Ibenmoussa; Ahmad Mohammad Salamatullah; Mohammed Bourhia; Gamal A. Shazly; Gezahign Fentahun Wondmie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Comparative efficacy of pharmacologic interventions in ulcerative colitis: a network meta analysis - Atta Ullah Khan; Maria Ali; Muhammad Aamir Wahab (Inflammopharmacology, 2025)
Introduction Ulcerative colitis is chronic inflammatory condition affecting the colon, necessitating remission inducing therapeutic interventions. With the emergence of newer more advanced options, their relative effectiveness remains unclear. This network meta-analysis (NMA) will compare the effectiveness of presently available biologics and small molecules in achieving and maintaining remission among patients of moderate-to-severe ulcerative colitis as part of induction and maintenance therapy. Methods A systematic search was conducted up to 21st February 2025, including only phase 2b/3 or 3 randomized controlled trials. The primary outcome was induction and maintenance of clinical remission (Full Mayo Score (FMS) ≤ 2, with no individual subscore > 1). Secondary outcomes assessed were clinical response, endoscopic improvement (Mayo Endoscopic Score (MES) ≤ 1 either with or without friability) and steroid free remission. Results Across 22 studies (7,683 patients), upadacitinib had the highest likelihood of inducing clinical remission (99.08%), clinical response (97.44%) and endoscopic improvement (99.32%), followed by Infliximab and guselkumab following close by for specific outcomes. In maintenance of clinical remission and endoscopic improvement upadacitinib again ranked highest (95.60%) and (99.46%). Tofacitinib (92.43%) has the highest probability with upadacitinib (87.73%) following behind in achieving steroid free remission. Conclusion Upadacitinib displayed high efficacy across multiple outcomes in both induction and maintenance therapy with Infliximab, guselkumab, and filgotinib following closely behind. For achieving steroid free remission tofacitinib has the highest probability of doing so. Overall small molecules and selective IL-23 inhibitors seems promising alternative to older biologics though additional head-to-head trial are warranted along with more real-world data.

Recovery, modifications, physicochemical properties, and MB removal efficiency of marble waste powder - Najm Us Saqib; Jamshid Abbas; Imran Ullah; Muhammad Abdul Haleem; Asma Aamir; Falak Zaman; Irfan Ullah (Environmental Science and Pollution Research, 2025)

Integrating physiological and molecular insights in cotton under cold stress conditions - Aamir Ali Abro; Muhammad Qasim; Mubashir Abbas; Noor Muhammad; Ijaz Ali; Shiguftah Khalid; Junaid Ahmed; Muhammad Waqas; Sezai Ercisli; Rashid Iqbal; Fang Liu (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Impact of elevated temperatures on the genetic and morpho-physiological traits of cotton genotypes cultivation - Aamir Ali Abro; Muhammad Qasim; Muhammad Usama Younas; Ijaz Ali; Mubashir Abbas; Noor Muhammad; Shiguftah Khalid; Junaid Ahmed; Umbreen Bibi; Muhammad Waqas; Sezai Ercisli; Fahad Al-Asmari; et al. (Genetic Resources and Crop Evolution, 2025)

Genome-wide identification and expression analysis of CYP450s under various stress treatment in Dendrobium huoshanense - Guohui Li; Xingen Zhang; Yuyue Li; Xilu Zhang; Muhammad Aamir Manzoor; Chuanbo Sun; Cheng Song; Min Zhang (Physiology and Molecular Biology of Plants, 2025)

Phenotypic and Molecular Screening for Yellow Rust Resistance in Chinese Wheat Hybrids as Impacted by Selection - Zainab Iftikhar; Muhammad Arif; Aamir Iqbal; Iqbal Munir; Sheng Quan Zhang; Chang Ping Zhao; Sajid Ali (Journal of Crop Health, 2025)
Exploring the potential of novel sources of wheat material is immensely important to combat the ever-changing pathogen causing wheat rust disease, associated with huge losses worldwide. This study focused on assessing rust (YR) resistance in Chinese wheat hybrids, combining molecular markers and field testing over two years with estimation of the impact of selection. Out of 416 hybrids, 108 were selected based on disease scoring parameters, showing negative genetic advancement for rust severity and coefficient of infection. The maximum rust severity reached 100% for four hybrids during the year 2017–18 whereas 70% for three hybrids during the year 2018–19. The maximum coefficient of infection was observed for four hybrids which were 100% (2017–18), whereas 70% for three hybrids (2018–19). Molecular genotyping with a set of five yellow rust resistance genes linked markers revealed that the most frequent molecular markers was Yr18 / Lr34 (among the YR markers), present in 92 out of 108 hybrids. All the five Yr genes were present only in 18 hybrids. Yr18 was the most common resistance gene detected in 85% hybrids, while Yr17 was the least detected gene (57%). Notably, the average coefficient of infection (ACI) was not directly associated with the number of resistant genes. Considering the overall performance, the hybrid lines 17BH002, 17BH057, 17BH073, 17BH109, 17BH123, 17BH128, 17BH190, 18BH026 and 17BH155 had an overall low yellow rust severity and co-efficient of infection and could be considering promising lines for further utilization. Clustering based on rust resistance genes categorized hybrids into five main clusters for YR resistance genes, showing variability among these valuable genetic resources. The observed variability in this study can be utilized for future breeding programs focused on developing resistant wheat varieties.

PavSPLs are key regulators of growth, development, and stress response in sweet cherry - Xunju Liu; Wanxia Sun; Haobo Liu; Li Wang; Muhammad Aamir Manzoor; Jiyuan Wang; Songtao Jiu; Caixi Zhang (Plant Science, 2025)

Allelic variation in major genes and quantitative trait loci associated with grain number in historical spring wheat cultivars - Muhammad Aamir Khan; Yuanyuan Tian; Humaira Qayyum; Benish Iltaf; Youshaa Danyal; Muhammad Amjad Farooq; Muhammad Kashif Ilyas; Zahid Mahmood; Shoaib-ur-Rehman; Jindong Liu; Awais Rasheed (Genetic Resources and Crop Evolution, 2025)

Reliable, Energy-Optimized, and Void-Aware (REOVA), Routing Protocol with Strategic Deployment in Mobile Underwater Acoustic Communications - Muhammad Umar Khan; Muhammad Aamir; Pablo Otero (Journal of Marine Science and Engineering, 2024)
The Underwater Acoustic Sensor Networks have gained significant attention because of their wide range of applications in submerged environments. However, ensuring reliable and energy-efficient communication in the submerged environment is challenging due to their distinctive characteristics such as limited energy resources, dynamic topology, extended propagation delays, and node mobility. Additionally, the void hole problem in submerged environments arises due to randomized node deployment. To curtail these issues, this paper introduces a novel way of strategically deploying the nodes based on the underwater depth parameters, which can reduce the likelihood of void hole occurrence. An optimal number of clusters based on the fixed transmission range of cluster heads is used to cater to extensive energy usage. In the proposed routing protocol, the path selection is based on the residual energy, link quality, and proximity to a higher number of nodes. Extensive simulations have been conducted by varying network parameters to analyze the network performance in terms of energy expenditure, packet delivery ratio, network throughput, number of dead nodes, and end-to-end delays. Also, the proposed work provides a performance comparison with some state-of-the-art protocols and exhibits promising results.

Exploring the chemistry of waste eggshells and its diverse applications - Laiba Iftikhar; Iqbal Ahmad; Muhammad Saleem; Aamir Rasheed; Amir Waseem (Waste Management, 2024)

Utilizing Cinnamomum verum (a culinary spice), as a functional food ingredient ameliorating hypercholesterolemia: In-vivo, in-vitro, and in-silico multi-model analysis - Mahnoor Bano; Muhammad Khurram Waqas; Talha Ali Chohan; Fakhra Batool; Aamir Mushtaq; Yahya I. Asiri; Mohd. Zaheen Hassan; Md Ali Mujtaba; Md. Khalid Anwer; Muhammad Irfan Sidique; Ayesha Riaz; Umair Khurshid; et al. (Food Bioscience, 2024)

Enabling Spatial Digital Twins: Technologies, Challenges, and Future Research Directions - Mohammed Eunus Ali; Muhammad Aamir Cheema; Tanzima Hashem; Anwaar Ulhaq; Muhammad Ali Babar (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2024)

Allelic variation in Puroindoline genes in synthetic hexaploid wheats and development of allele-specific PCR markers for new soft-texture alleles - Muhammad Aamir Khan; Yuanyuan Tian; Humaira Qayyum; Awais Rasheed; Zhonghu He (Cereal Research Communications, 2024)

Polygonum bistorta Linn. as a green source for synthesis of biocompatible selenium nanoparticles with potent antimicrobial and antioxidant properties - Hafiz Abdul Haseeb; Muhammad Aslam Khan; Hassam Rasheed; Muhammad Usman Zahid; Thu Dung Doan; Muhammad Aamir Ramzan Siddique; Uzair Ahmad; Syed Ali Imran Bokhari (BioMetals, 2024)

Data-driven exploration in complex basins: A critical aspect of new prospect delineation in thin sands using simultaneous seismic inversion - Urooj Shakir; Aamir Ali; Muyyassar Hussain; Ahmed E Radwan; Ahmed Abd El Aal; Muhammad Raiees Amjad; Muhammad Fahad Mahmood (Journal of Earth System Science, 2024)

A comprehensive review of deep learning techniques for salt dome segmentation in seismic images - Muhammad Saif Ul Islam; Aamir Wali (Journal of Applied Geophysics, 2024)

Proximate composition and prevalence and exposure assessment of aflatoxins intake through consumption of fresh carrot and processed marketed carrot products in South Punjab, Pakistan - Aneela Nijabat; Shahwana Bibi; Maryam Ajmal; Saher Nawaz; Muhammad Zaheer Sajid; Saad Ullah Khan Leghari; Muhammad Mahmood-ur-Rehman; Naima Huma Naveed; Aamir Ali; Philipp W. Simon (Natural Product Research, 2024)

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

From lake to fisheries: Interactive effect of climate and landuse changes hit on lake fish catch? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Majid Rasta; Caihong Hu; Chengshuai Liu; Yinghai Li; Ao li; Jijun Chen; Chunyun Zhu; Sher Ali; Jiali Guo; et al. (Environmental Research, 2024)

Decoupling numerical method based on deep neural network for nonlinear degenerate interface problems - Chen Fan; Muhammad Aamir Ali; Zhiyue Zhang (Computer Physics Communications, 2024)

Colimoxin influences on the anaerobic co-digestion performance of chicken manure and wheat straw: volatile fatty acids generation and utilization trends and regression modelling - Muhammad Aamir; Muhammad Hassan (Environment, Development and Sustainability, 2024)

Optimizing cultural conditions and pretreatment for high-value single-cell protein from vegetable waste - Hafiz Muhammad Aamir Shahzad; Zukhruf Asim; Khaled A. Mahmoud; Omer M.A. Abdelhadi; Fares Almomani; Kashif Rasool (Process Safety and Environmental Protection, 2024)

Appraisal of Urban Waterlogging and Extent Damage Situation after the Devastating Flood - Shan-e-hyder Soomro; Muhammad Waseem Boota; Xiaotao Shi; Gul-e-Zehra Soomro; Yinghai Li; Muhammad Tayyab; Caihong Hu; Chengshuai Liu; Yuanyang Wang; Junaid Abdul Wahid; Mairaj Hyder Alias Aamir Soomro; Jiali Guo; et al. (Water Resources Management, 2024)

Alleviating Drought Stress in Strawberry Plants: Unraveling the Role of Paclobutrazol as a Growth Regulator and Reducer of Oxidative Stress Induced by Reactive Oxygen and Carbonyl Species - Khansa Saleem; Muhammad Ahsan Asghar; Ali Raza; Kaiwen Pan; Abd Ullah; Hafiz Hassan Javed; Mahmoud F. Seleiman; Shakeel Imran; Sajid Mehmood Nadeem; Khurram Shehzad Khan; Junbo Du; Fei Xu; et al. (Journal of Plant Growth Regulation, 2024)

Quantification and polymeric characterization of microplastics in composts and their accumulation in lettuce - Aamna Naeem; Muhammad Ansar Farooq; Muhammad Shafiq; Muhammad Arshad; Aamir Alaud Din; Abdulrahman Ali Alazba (Chemosphere, 2024)

Assessment of carcinogenic and non-carcinogenic risk of exposure to potentially toxic elements in tea infusions: Determination by ICP-OES and multivariate statistical data analysis - Mahmood Ahmed; Muhammad Ahmad; Muhammad Ayyan Khan; Aamir Sohail; Mudassar Sanaullah; Waqar Ahmad; Dure Najaf Iqbal; Khuram Khalid; Tanveer A. Wani; Seema Zargar (Journal of Trace Elements in Medicine and Biology, 2024)

Dynamic nexus among fossil fuels utilization, economic growth, and urbanization: a tri-regional selected countries analysis - Muhammad Aamir; Jamshaid ur Rehman (Environmental Science and Pollution Research, 2024)

Differential involvement of PEBP genes in early flowering of Peucedanum praeruptorum Dunn - Cheng Song; Wenwu Zhang; Muhammad Aamir Manzoor; Irfan Ali Sabir; Haoyu Pan; Luxi Zhang; Yingyu Zhang (Postharvest Biology and Technology, 2024)

Tailored design of CO2-selective mixed-matrix membranes using nitrile-functionalized COFs as 2D nanofillers - Bosirul Hoque; Mohd Yusuf Khan; Aamir Hanif; Mahmoud Abdelnaby; Aasif Helal; Abuzar Khan; Muhammad Usman; Qasem Ahmed Drmosh (Journal of Environmental Chemical Engineering, 2024)

Heavy Metal Stress in Medicinal Plants: Detoxification Mechanisms, Antioxidants, and Implications for Human Health - Muhammad Waheed Riaz; Tong Wu; Quaid Hussain; Fasih Ullah Haider; Weiwei Jiang; Qingsong Shao; Muhammad Aamir Manzoor; Bingcong Xing (Journal of Soil Science and Plant Nutrition, 2024)

Soil Organic Carbon and Nitrogen Mineralization Potential of Manures Regulated by Soil Microbial Activities in Contrasting Soil Textures - Waqar Ahmed; Muhammad Nadeem Ashraf; Muhammad Sanaullah; Muhammad Aamir Maqsood; Muhammad Ahmed Waqas; Shafeeq Ur Rahman; Saddam Hussain; Hammad Raza Ahmad; Adnan Mustafa; Xu Minggang (Journal of Soil Science and Plant Nutrition, 2024)

Challenges and opportunities in biogas conversion to microbial protein: A pathway for sustainable resource recovery from organic waste - Hafiz Muhammad Aamir Shahzad; Fares Almomani; Asif Shahzad; Khaled A. Mahmoud; Kashif Rasool (Process Safety and Environmental Protection, 2024)

How effective is twitter (X) social media data for urban flood management? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Gul-e-Zehra Soomro; Xiaotao Shi; Jiali Guo; Yinghai Li; Muhammad Tayyab; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Chengshuai Liu; Yuanyang Wang; et al. (Journal of Hydrology, 2024)

Modulating plant-soil microcosm with green synthesized ZnONPs in arsenic contaminated soil - Asad Rehman; Saeed ur Rahman; Pengli Li; Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Muhammad Azam; Junfeng Cao; Muhammad Sanaullah Malik; Mouna Jeridi; Naveed Ahmad; Khulood Fahad Alabbosh; Qunlu Liu; et al. (Journal of Hazardous Materials, 2024)

Exogenous Salicylic Acid Improves Photosynthetic and Antioxidant Capacities and Alleviates Adverse Effects of Cherry Rootstocks Under Salt Stress - Jieming Xu; Yan Xu; Yuxuan Wang; Zhengxin Lv; Xunju Liu; Wanxia Sun; Muhammad Aamir Manzoor; Ruie Liu; Shiping Wang; Songtao Jiu; Caixi Zhang (Journal of Plant Growth Regulation, 2024)

Clubroot (Plasmodiophora brassicae) Suppression Under Biocontrol Agents in Pak choi with Variations in Physiological, Biochemical, and Bacterial Diversity - Shazma Gulzar; Fiza Liaquat; Muhammad Khalid Hameed; Asad Rehman; Muhammad Salman Zahid; Muhammad Aamir Manzoor; Iftikhar Hussain Shah; Yidong Zhang (Journal of Plant Growth Regulation, 2024)

An appealing review of industrial and nutraceutical applications of pistachio waste - Syed Ali Hassan; Mueen Abbas; Sania Zia; Abid Aslam Maan; Muhammad Kashif Iqbal Khan; Abdo Hassoun; Aamir Shehzad; Richard Gattin; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2024)

Horticulture crop under pressure: Unraveling the impact of climate change on nutrition and fruit cracking - Muhammad Aamir Manzoor; Yan Xu; Zhengxin lv; Jieming Xu; Iftikhar Hussain Shah; Irfan Ali Sabir; Yuxuan Wang; Wanxia Sun; Xunju Liu; Li Wang; Ruie Liu; Songtao Jiu; et al. (Journal of Environmental Management, 2024)

Comparative genomics of N-acetyl-5-methoxytryptamine members in four Prunus species with insights into bud dormancy and abiotic stress responses in Prunus avium - Muhammad Aamir Manzoor; Yan Xu; Zhengxin lv; Jieming Xu; Yuxuan Wang; Wanxia Sun; Xunju Liu; Li Wang; Muhammad Abdullah; Ruie Liu; Songtao Jiu; Caixi Zhang (Plant Cell Reports, 2024)

Genome-wide identification and expression analysis of TIFY genes under MeJA, cold and PEG-induced drought stress treatment in Dendrobium huoshanense - Guohui Li; Muhammad Aamir Manzoor; Rui Chen; Yingyu Zhang; Cheng Song (Physiology and Molecular Biology of Plants, 2024)

Genetics aspect of vitamin C (Ascorbic Acid) biosynthesis and signaling pathways in fruits and vegetables crops - Adnan Sami; Shiming Han; Muhammad Zeshan Haider; Rameen Khizar; Qurban Ali; Muhammad Shafiq; Javaria Tabassum; Muhammad Nouman Khalid; Muhammad Arshad Javed; Mateen Sajid; Muhammad Aamir Manzoor; Irfan Ali Sabir (Functional & Integrative Genomics, 2024)

Scorpion sting in Hafizabad, Pakistan: Facility based epidemiological study - Muhammad Mohsin Ahsan; Zoya Gulzar; Hafiz Muhammad Tahir; Aamir Ali; Muhammad Ismail; Muhammad Khalid Mukhtar; Zain Ul Abdin (Toxicon, 2024)

Foot and mouth disease (FMD) epidemiology in small ruminants by identifying antibodies for non-structural and structural proteins with a sequential screening approach: A cross-sectional study - Muhammad Shakeel Khaliq; Mobeen Sarwar; Farhat Nazir Awan; Halima Sadia; Aamir Saleem; Syed Abdul Khaliq; Muhammad Hassan Mushtaq; Mamoona Chaudhry; Abdul Rehman (Small Ruminant Research, 2024)

Comprehensive review: Effects of climate change and greenhouse gases emission relevance to environmental stress on horticultural crops and management - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Wu Jinhui; Xuyang Li; Muhammad Khalid Hameed; Asad Rehaman; Pengli Li; Yidong Zhang; Qingliang Niu; Liying Chang (Journal of Environmental Management, 2024)

Beyond contamination: Enhancing plant tolerance to arsenic through phytobial remediation - Saeed ur Rahman; Xinxin Liu; Muhammad Khalid; Asad Rehman; Junfeng Cao; Sadaf-Ilyas Kayani; Muhammad Naeem; Naveed Ahmad; Abid Ali Khan; Muhammad Aamir Manzoor; Chang Zhao; Haoxin Tan; et al. (South African Journal of Botany, 2024)

Green economy transition in Asia Pacific: A holistic assessment of renewable energy production - Yi Lin; Muhammad Aamir Mahmood; Wentao Meng; Qamar Ali (Journal of Cleaner Production, 2024)

Unraveling the combined deleterious effects of ochratoxin A and atrazine upon broiler’s health: Toxicopathological, serum biochemical and immunological perspectives - Aisha Khatoon; Muhammad Yasir Nawaz; Ghazala Mehboob; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Rao Zahid Abbas; Muhammad Umar Ijaz; Bilal Murtaza; Sheraz Ahmed Bhatti; Zain ul Abidin; Aamir Riaz Khan (Toxicon, 2023)

Bacterial inoculation remediates heavy metals toxicity through modulating biochemicals and antioxidant enzymes of Daucus carota L. grown in lead contaminated soil - Naima Huma Naveed; Naveed Abbas Nasir; Anis Ali Shah; Tahir Shahzad; Nasim Ahmad Yasin; Zain Ali; Muhammad Jamil; Talha Javed; Aamir Ali (South African Journal of Botany, 2023)

Characterizing the HMA gene family in dragon fruit (Selenicereus undatus L.) and revealing their response to multifactorial stress combinations and melatonin-mediated tolerance - Qamar U Zaman; Latif Ullah Khan; Muhammad Azhar Hussain; Asif Ali; Liu Hui; Aamir Ali Khokhar; Darya Khan; Hua-Feng Wang (South African Journal of Botany, 2023)

Field response and molecular screening of European wheat germplasm against powdery mildew at the Himalayan region of Pakistan - Aamir Iqbal; Zia Ur Rehman; Muhammad Rameez Khan; Amir Muhammad Khan; Shahid Ullah Khan; Muhammad Arif; Javaid Iqbal; Mujeeb Ur Rehman; Minhaj Ali; Muhammad Qasim; Imran Ali; Zakir Hussain Facho; et al. (Journal of Applied Genetics, 2023)

Correction to: Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Short- and medium-chain chlorinated paraffins in agricultural and industrial soils from Shanghai, China: surface and vertical distribution, penetration behavior, and health risk assessment - Chenye Xu; Quan Zhou; Chensi Shen; Fang Li; Shuren Liu; Shanshan Yin; Muhammad Aamir (Environmental Geochemistry and Health, 2023)

Analysis of coumarin content and key enzyme genes expression involved in coumarin biosynthesis from Peucedanum praeruptorum Dunn at different stages - Peipei Wei; Yaobiqi Li; Cheng Song; Muhammad Aamir Manzoor; Jun Dai; Qihui Yin; Yanmei Zhang; Bangxing Han (Acta Physiologiae Plantarum, 2023)

Variations of b-value and the ω-upper bound magnitude of GIII distribution of the Pamir–Hindu Kush region - Khaista Rehman; Wajid Ali; Muhammad Shafique; Aamir Ali; Adnan Barkat; Waqas Ahmed; Muhammad Waqar Azeem (Arabian Journal of Geosciences, 2023)

Utilization of cereal-based husks to achieve sustainable development goals: Treatment of wastewater, biofuels, and biodegradable packaging - Syed Ali Hassan; Mueen Abbas; Waqar Mujahid; Waqar Ahmed; Saeed Ahmad; Abid Aslam Maan; Aamir Shehzad; Zuhaib F. Bhat; Rana Muhammad Aadil (Trends in Food Science & Technology, 2023)

Exogenous melatonin mitigates chilling injury in zucchini fruit by enhancing antioxidant system activity, promoting endogenous proline and GABA accumulation, and preserving cell wall stability - Sajid Ali; Aamir Nawaz; Safina Naz; Maratab Ali; Shaghef Ejaz; Muhammad Azam; Kashif Razzaq (Postharvest Biology and Technology, 2023)

Integrating compound-specific stable isotope and enantiomer-specific analysis to characterize the isomeric and enantiomeric signatures of hexachlorocyclohexanes (HCHs) in paddy soils - Muhammad Aamir; Zili Guo; Jiawei Yu; Lu Zhao; Dongmei Xu; Xiaohui Sun; Chao Xu; Lili Niu; Weiping Liu (Journal of Hazardous Materials, 2023)

Cellulose-based adsorbent materials for water remediation: Harnessing their potential in heavy metals and dyes removal - Awais Ali Aslam; Sadaf Ul Hassan; Muhammad Haris Saeed; Osama Kokab; Zulfiqar Ali; Muhammad Shahid Nazir; Waleed Siddiqi; Aamir Ali Aslam (Journal of Cleaner Production, 2023)

Comparative appraisal of groundwater quality in lower and upper riparians of Malir River system through geospatial techniques - Syed Wasi Haider; Syed Jamil Hasan Kazmi; Aamir Alamgir; Adnan Khan; Muhammad Arsalan (Arabian Journal of Geosciences, 2023)

Co-application of copper oxide nanoparticles and Trichoderma harzianum with physiological, enzymatic and ultrastructural responses for the mitigation of salt stress - Iftikhar Hussain Shah; Irfan Ali Sabir; Asad Rehman; Muhammad Khalid Hameed; Gadah Albashar; Muhammad Aamir Manzoor; Awais Shakoor (Chemosphere, 2023)

Alleviation of arsenic toxicity-induced oxidative stress in lemon grass by methyl jasmonate - Khansa Saleem; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Ali Raza; Mahmoud F. Seleiman; Abd Ullah; Altafur Rahman; Sufyan Iqbal; Aamir Hanif; Shakeel Imran; Sajid Mahmood Nadeem; Junbo Du; et al. (South African Journal of Botany, 2023)

Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Exploring the Intertwined Nexus between Globalization, Energy Usage, Economic Complexity, and Environmental Quality in Emerging Asian Economies: A Pathway Towards a Greener Future - Muhmmad Asim Rafiq; Abdul Rauf; Saifullah Shakir; Ameer Muhammad Aamir Abbas; Huaping Sun; Saira Abid (Environmental Science and Pollution Research, 2023)

Fabrication and Evaluation of Anticancer Potential of Eugenol Incorporated Chitosan-Silver Nanocomposites: In Vitro, In Vivo, and In Silico Studies - Hamid Saeed Shah; Sumera Zaib; Muhammad Sarfraz; A. Alhadhrami; Mohamed M. Ibrahim; Aamir Mushtaq; Faisal Usman; Memoona Ishtiaq; Muhammad Sajjad; Hafiz Muhammad Mazhar Asjad; Umar Farooq Gohar (AAPS PharmSciTech, 2023)

Role of depositional and diagenetic controls on reservoir quality of complex heterogenous tidal sandstone reservoirs: An example from the Lower Goru formation, Middle Indus Basin, Southwest Pakistan - Muhammad Asif Khan; Tahseenullah Khan; Aamir Ali; Abdulwahab Muhammad Bello; Ahmed E. Radwan (Marine and Petroleum Geology, 2023)

Bifunctional electrocatalytic water splitting augmented by cobalt-nickel-ferrite NPs-supported fluoride-free MXene as a novel electrocatalyst - Tabinda Rasheed; Aamir Rasheed; Fatimah Mohammed A. Alzahrani; Sara Ajmal; Muhammad Farooq Warsi; M.S. Al-Buriahi; Ghulam Dastgeer; Seung Goo Lee (Fuel, 2023)

Environmental sustainable: Biogenic copper oxide nanoparticles as nano-pesticides for investigating bioactivities against phytopathogens - Muhammad Aamir Manzoor; Iftikhar Hussain Shah; Irfan Ali Sabir; Ajaz Ahmad; Gadah Albasher; Afzal Ahmed Dar; Muhammad Ahsan Altaf; Awais Shakoor (Environmental Research, 2023)

Effects of melatonin and Trichoderma harzianum on pak choi yield, chlorophyll contents and antioxidant defense system under clubroot disease - Shazma Gulzar; Muhammad Aamir Manzoor; Fiza Liaquat; Iftikhar Hussain Shah; Asad Rehman; Muhammad Khalid Hameed; Samiah Arif; Xuanwei Zhou; Yidong Zhang (South African Journal of Botany, 2023)

Application of UAV photogrammetry and electrical resistivity tomography for characterization of a complex landslide: a case study from northwest Himalayas, Pakistan - Syed Ahatsham Haider; Matloob Hussain; Aamir Ali; Muhammad Faheem Abbasi; Saad Wani (Natural Hazards, 2023)

Evaluation of phytoremediation potential and resistance of Gladiolus grandiflora L. against cadmium stress - Syed Ali Qasim Bukhari; Aamir Nawaz; Muhammad Dawood (Environmental Geochemistry and Health, 2023)

Advanced Data Processing as a Tool to Enhance the Vertical and Horizontal Resolution of Bottom Simulating Reflector (BSR): Implications for GAS Hydrate Exploitation - Muhammad Kamal; Aamir Ali; Yawar Amin; Asam Farid; Bakhtawar Sarosh (Pure and Applied Geophysics, 2023)

Endophytic bacterial diversity by 16S rRNA gene sequencing of Pak choi roots under fluazinam, Trichoderma harzianum, and Sophora flavescens inoculation - Shazma Gulzar; Muhammad Aamir Manzoor; Fiza Liaquat; Muhammad Salman Zahid; Samiah Arif; Xuanwei Zhou; Yidong Zhang (Functional & Integrative Genomics, 2023)

Insights to Gossypium defense response against Verticillium dahliae: the Cotton Cancer - Muhammad Jawad Umer; Jie Zheng; Mengying Yang; Raufa Batool; Aamir Ali Abro; Yuqing Hou; Yanchao Xu; Haileslassie Gebremeskel; Yuhong Wang; ZhongLi Zhou; Xiaoyan Cai; Fang Liu; et al. (Functional & Integrative Genomics, 2023)

Influence of Co3O4-based catalysts on N2O catalytic decomposition and NO conversion - Abrar Inayat; Lisandra Rocha-Meneses; Muhammad Ayoub; Sami Ullah; Ahmad Z. Abdullah; Salman R. Naqvi; Aamir H. Bhat (Environmental Science and Pollution Research, 2023)

Enhancing carbon capture efficiency of zeolite-embedded polyether sulfone mixed-matrix membranes via annealing process - Aamir Sohail; Muhammad Sarfraz; Sidra Nawaz; Zaman Tahir (Journal of Cleaner Production, 2023)

High prevalence of extensively drug resistant and extended spectrum beta lactamases (ESBLs) producing uropathogenic Escherichia coli isolated from Faisalabad, Pakistan - Beenish Ehsan; Asma Haque; Muhammad Qasim; Aamir Ali; Yasra Sarwar (World Journal of Microbiology and Biotechnology, 2023)

Dose optimization of silicon for boosting arbuscular mycorrhizal fungi colonization and cadmium stress mitigation in maize (Zea mays L.) - Ubaid Ullah Zia; Abdul Rehman Niazi; Zahoor Ahmad; Hesham F. Alharby; Ejaz Ahmad Waraich; Asim Abbasi; Muhammad Aamir Iqbal; Sarfraz Ahmed; Shozab Hina (Environmental Science and Pollution Research, 2023)

Optimization of Citric Acid and EDTA Levels Under Ni Stress Using Rapeseed Brassica napus L. for Phytoremediation - Humera Nawaz; Naila Asghar; Aamir Ali; Amina Ameer; Muhammad Asif Shehzad; Fahim Nawaz; Ansar Mehmood; Muhammad Sajjad Iqbal; Ummar Iqbal; Muhammad Kaleem; Ameer Khan; Khawaja Shafique Ahmad (Water, Air, & Soil Pollution, 2023)

Occurrence and completed genomes of sweet potato chlorotic stunt virus infecting sweet potato in Korea - Nattanong Bupi; Hee-Seong Byun; Aamir Lal; Thuy Thi Bich Vo; Muhammad Amir Qureshi; Eui-Joon Kil; Youngjae Chung; Taek-Kyun Lee; Sukchan Lee (European Journal of Plant Pathology, 2023)

The dynamic impact of renewable energy consumption, trade, and financial development on carbon emissions in low-, middle-, and high-income countries - Nasrullah Nasrullah; Muhammad Iftikhar ul Husnain; Muhammad Aamir Khan (Environmental Science and Pollution Research, 2023)

Legacy and novel brominated flame retardants in agricultural soils of eastern China (2011–2021): Concentration level, temporal trend, and health risk assessment - Qi An; Lina Yang; Shengchao Yang; Yanting Wang; Long Shi; Muhammad Aamir; Weiping Liu (Journal of Hazardous Materials, 2023)

Phytotoxic effects of chemically synthesized copper oxide nanoparticles induce physiological, biochemical, and ultrastructural changes in Cucumis melo - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Fiza Liaquat; Shazma Gulzar; Liying Chang; Yidong Zhang (Environmental Science and Pollution Research, 2023)

Insight into potent TLR2 inhibitors for the treatment of disease caused by Mycoplasma pneumoniae based on machine learning approaches - Muhammad Ishfaq; Ziaur Rahman; Muhammad Aamir; Ihsan Ali; Yurong Guan; Zhihua Hu (Molecular Diversity, 2023)

Polymeric Nanogel for Oral Delivery of the Chemotherapeutic Agent: Fabrication and Evaluation Alongside Toxicological Studies and Histopathological Examination - Humaira Sultana; Muhammad Naeem Aamir; Asadullah Madni; Masood ur Rehman; Afifa Shafiq; Jafir Hussain Shirazi; Sidra Hassan; Sumaira (AAPS PharmSciTech, 2023)

Zeolite amendment reduces lead accumulation and improves growth and yield in tomato plants irrigated with sewage water - Rashid Jawad; Aamir Nawaz; Shaghef Ejaz; Sajid Ali; Muhammad Shahzad Saleem; Hafiz Mohkum Hammad (Environmental Science and Pollution Research, 2023)

Foliar application of silicon-based nanoparticles improve the adaptability of maize (Zea mays L.) in cadmium contaminated soils - Sarfraz Ahmed; Muhammad Iqbal; Zahoor Ahmad; Muhammad Aamir Iqbal; Arkadiusz Artyszak; Ayman E. L. Sabagh; Hesham F. Alharby; Akbar Hossain (Environmental Science and Pollution Research, 2023)

Assessment of aflatoxin M 1 exposure and associated determinants in children from Lahore, Pakistan - Waseela Ashraf; Abdul Rehman; Mansur-ud-Din Ahmad; Masood Rabbani; Muhammad Hassan Mushtaq; Khalida Aamir; Fareeha Akhtar; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2023)

Congener profiles, air-soil exchange, and potential risks of short- and medium-chain chlorinated paraffins in demonstration zone of Yangtze River Delta - Quan Zhou; Chenye Xu; Chensi Shen; Fang Li; Shuren Liu; Muhammad Aamir (Atmospheric Pollution Research, 2023)

Assessment of wild turmeric–based eco-friendly yellow natural bio-colorant for dyeing of wool fabric - Noman Habib; Aamir Ali; Shahid Adeel; Fazal-ur-Rehman; Muhammad Aftab; Asma Inayat (Environmental Science and Pollution Research, 2023)

Analyzing past and future trends in Pakistan’s groundwater irrigation development: implications for environmental sustainability and food security - Amar Razzaq; Hancheng Liu; Meizhen Xiao; Khalid Mehmood; Muhammad Aamir Shahzad; Yewang Zhou (Environmental Science and Pollution Research, 2022)

Impact of economic and green growth on poverty, income inequalities, and environmental degradation: a case of South Asian economies - Shazia Kousar; Aamir Inam Bhutta; Muhammad Rizwan Ullah; Aiza Shabbir (Environmental Science and Pollution Research, 2022)

Recent trends in green synthesis of silver, gold, and zinc oxide nanoparticles and their application in nanosciences and toxicity: a review - Muhammad Musaddiq Shah; Khurshid Ahmad; Bashir Ahmad; Shahid Masood Shah; Hamid Masood; Muhammad Aamir Ramzan Siddique; Rasheed Ahmad (Nanotechnology for Environmental Engineering, 2022)

Evaluating the safety and efficacy of daprodustat for anemia of chronic kidney disease: a meta-analysis of randomized clinical trials - Kaneez Fatima; Warda Ahmed; Asad Saulat Fatimi; Omar Mahmud; Muhammad Umar Mahar; Ayesha Ali; Syed Roohan Aamir; Muhammad Taha Nasim; Muhammad Bilal Islam; Muhammad Talha Maniya; Dua Azim; Shayan Marsia; et al. (European Journal of Clinical Pharmacology, 2022)

Amelioration of lead toxicity by ascorbic acid in sugarcane (Saccharum officinarum L.) under in vitro condition - Yasmeen Saleem; Aamir Ali; Shagufta Naz; Muhammad Jamil; Naima Huma Naveed (Environmental Science and Pollution Research, 2022)

A green and environmental sustainable approach to synthesis the Mn oxide nanomaterial from Punica granatum leaf extracts and its in vitro biological applications - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Shazma Gulzar; Liying Chang; Yidong Zhang (Environmental Monitoring and Assessment, 2022)

A novel lens of stock market capitalization and environmental degradation - Aamir Azeem; Muhammad Akram Naseem; Naveed Ul Hassan; Ijaz Butt; Muhammad Toseef Aslam; Shahid Ali; Atif khan Jadoon (Environmental Science and Pollution Research, 2022)

Determination and detoxification of aflatoxin and ochratoxin in maize from different regions of Pakistan - Syed Wajih ul Hassan Shah Gillani; Yumna Sadef; Muhammad Imran; Hafiz Muhammad Fahad Raza; Aamir Ghani; Sumera Anwar; Muhammad Yasin Ashraf; Shabbir Hussain (Environmental Monitoring and Assessment, 2022)

Assessment of aflatoxin B 1 -lysine adduct in children and its effect on child growth in Lahore, Pakistan - Waseela Ashraf; Abdul Rehman; Mansur-ud-Din Ahmad; Masood Rabbani; Muhammad Hassan Mushtaq; Khalida Aamir; Kathy S. Xue; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2022)

Immunological characterization of chitosan adjuvanted outer membrane proteins of Salmonella enterica serovar Typhi as multi-epitope typhoid vaccine candidate - Ambreen Ayub; Muhammad Usman; Ayesha Ihsan; Quratul Ain; Asad Bashir Awan; Muhammad Wajid; Aamir Ali; Abdul Haque; Mazhar Iqbal; Yasra Sarwar (Molecular Biology Reports, 2022)

Genome-wide identification and comparative analysis of MATE gene family in Cucurbitaceae species and their regulatory role in melon (Cucumis melo) under salt stress - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Fazal Haq; Samiah Arif; Muhammad Abdullah; Qingliang Niu; Yidong Zhang (Horticulture, Environment, and Biotechnology, 2022)

Evaluating dual exposure by using climate-conflict vulnerability index on the coastal districts of Sindh, Pakistan - Noor Fatima; Aamir Alamgir; Moazzam Ali Khan; Muhammad Owais (Environmental Monitoring and Assessment, 2022)

Examining the Effects of Normal Ageing on Cortical Connectivity of Older Adults - Muhammad Aamir Panhwar; Muhammad Mohsin Pathan; Nasrullah Pirzada; Muhammad Aashed Khan Abbasi; Deng ZhongLiang; Ghazala Panhwar (Brain Topography, 2022)

Clean and sustainable transportation through electric vehicles — a user survey of three-wheeler vehicles in Pakistan - Mohammad Aamir Khan; Syed Fawad Bokhari; Aazir Khan; Muhammad Saad Amjad; Arooj Mobasher Butt; Muhammad Zeeshan Rafique (Environmental Science and Pollution Research, 2022)

Do geopolitical risk and energy consumption contribute to environmental degradation? Evidence from E7 countries - Muhammad Iftikhar ul Husnain; Qasim Raza Syed; Arooj Bashir; Muhammad Aamir Khan (Environmental Science and Pollution Research, 2022)

River Flood Susceptibility and Basin Maturity Analyzed Using a Coupled Approach of Geo-morphometric Parameters and SWAT Model - Shan-e-hyder Soomro; Caihong Hu; Muhammad Waseem Boota; Zubair Ahmed; Liu Chengshuai; Han Zhenyue; Li Xiang; Mairaj Hyder Alias Aamir Soomro (Water Resources Management, 2022)

Landslide Susceptibility Mapping Using Machine Learning Algorithm: A Case Study Along Karakoram Highway (KKH), Pakistan - Muhammad Afaq Hussain; Zhanlong Chen; Isma Kalsoom; Aamir Asghar; Muhammad Shoaib (Journal of the Indian Society of Remote Sensing, 2022)

Non-toxic nature of chebulinic acid on biochemical, hematological and histopathological analysis in normal Sprague Dawley rats - Khurram Aamir; Vaisnevee Sugumar; Hidayat Ullah Khan; Chung Yeng Looi; Rajesh Juneja; Muhammad Waqas; Aditya Arya (Toxicological Research, 2022)

Glioblastoma Therapy: Rationale for a Mesenchymal Stem Cell-based Vehicle to Carry Recombinant Viruses - Sakhawat Ali; Qin Xia; Tahir Muhammad; Liqun Liu; Xinyi Meng; David Bars-Cortina; Aamir Ali Khan; Yinghui Huang; Lei Dong (Stem Cell Reviews and Reports, 2022)

Nitrification Inhibitor and Plant Growth Regulators Improve Wheat Yield and Nitrogen Use Efficiency - Khadim Dawar; Umar Rahman; Syed Sartaj Alam; Mohammad Tariq; Aamir Khan; Shah Fahad; Rahul Datta; Subhan Danish; Shah Saud; Muhammad Noor (Journal of Plant Growth Regulation, 2022)

A Review of Antimicrobial Peptides: Its Function, Mode of Action and Therapeutic Potential - Sehrish Nayab; Muhammad Aamir Aslam; Sajjad ur Rahman; Zia ud Din Sindhu; Sanaullah Sajid; Nishat Zafar; Maida Razaq; Rabia Kanwar; Amanullah (International Journal of Peptide Research and Therapeutics, 2022)

In vitro α-glycosidase and urease enzyme inhibition profile of some selected medicinal plants of Pakistan - Abdur Rauf; Saud Bawazeer; Muhammad Naseer; Fahad A. Alhumaydhi; Abdullah S. M. Aljohani; Aamir Habib; Raheem Khan; Urooj Jehan; Muhammad Nasimullah Qureshi; Majid Khan; Umar Farooq; Amirzhan Kassenov; et al. (Natural Product Research, 2021)

Assessment of Hg accumulation in fish and scalp hair in fishing communities along river Swat, Pakistan - Muhammad Aamir Munir; Bushra Khan; Ishaq Ahmed Mian; Muhammad Rafiq; Samreen Shahzadi; Kashif Naeem; Iqbal Ahmad (Environmental Science and Pollution Research, 2021)

Mapping flood extend and its impact on land use/land cover and settlements variations: a case study of Layyah District, Punjab, Pakistan - Shan-e-hyder Soomro; Caihong Hu; Muhammad Waseem Boota; Mairaj Hyder Alias Aamir Soomro; Shengqi Jian; Zeeshan Zafar; Xiaoping Li (Acta Geophysica, 2021)

Constituents and antibacterial activity of leaf essential oil of Plectranthus scutellarioides - Pakeeza Aziz; Nadeem Muhammad; Azeem Intisar; Muhammad Amin Abid; Muhammad Imran Din; Muhammad Yaseen; Rehana Kousar; Aqsa Aamir; Quratulain; Rabia Ejaz (Plant Biosystems, 2021)

An empirical investigation of nuclear energy and environmental pollution nexus in India: fresh evidence using NARDL approach - Aamir Aijaz Syed; Muhammad Abdul Kamal; Ravindra Tripathi (Environmental Science and Pollution Research, 2021)

Development of empirical correlations for limit equilibrium methods of slope stability analysis - Muhammad Aamir Moawwez; Ji-Peng Wang; Muhammad Awais Hussain (Arabian Journal of Geosciences, 2021)

Testing dependence patterns of energy consumption with economic expansion and trade openness through wavelet transformed coherence in top energy-consuming countries - Muhammad Iftikhar ul Husnain; Nasrullah; Muhammad Aamir Khan (Environmental Science and Pollution Research, 2021)

Emamectin benzoate induced enzymatic and transcriptional alternation in detoxification mechanism of predatory beetle Paederus fuscipes (Coleoptera: Staphylinidae) at the sublethal concentration - Muhammad Musa Khan; Aamir Hamid Khan; Muhammad Waqar Ali; Muhammad Hafeez; Shahbaz Ali; Cailian Du; Zeyun Fan; Muzammil Sattar; Hongxia Hua (Ecotoxicology, 2021)

Drought Tolerance Strategies in Plants: A Mechanistic Approach - Muhammad Ilyas; Mohammad Nisar; Nadeem Khan; Ali Hazrat; Aamir Hamid Khan; Kashif Hayat; Shah Fahad; Aziz Khan; Abid Ullah (Journal of Plant Growth Regulation, 2021)

Application of model based post-stack inversion in the characterization of reservoir sands containing porous, tight and mixed facies: A case study from the Central Indus Basin, Pakistan - Muhammad Toqeer; Aamir Ali; Tiago M Alves; Ashar Khan; Zubair; Matloob Hussain (Journal of Earth System Science, 2021)

Investigating India’s pollution-intensive ‘dirty’ trade specialisation: analysis with ‘revealed symmetric comparative advantage’ index - Suvajit Banerjee; Somnath Hazra; Muhammad Aamir Khan; Muhammad Iftikhar ul Husnain (Environmental Science and Pollution Research, 2021)

Does the environmental Kuznets curve reliably explain a developmental issue? - Muhammad Iftikhar Ul Husnain; Azad Haider; Muhammad Aamir Khan (Environmental Science and Pollution Research, 2021)

An overview of genetic mutations and epigenetic signatures in the course of pancreatic cancer progression - Aamir Ali Khan; Xinhui Liu; Xinlong Yan; Muhammad Tahir; Sakhawat Ali; Hua Huang (Cancer and Metastasis Reviews, 2021)

Effect of Seawater Ageing on Fracture Toughness of Stitched Glass Fiber/Epoxy Laminates for Marine Applications - Atizaz Hassan; Rafiullah Khan; Numan Khan; Muhammad Aamir; Danil Yurievich Pimenov; Khaled Giasin (Journal of Marine Science and Engineering, 2021)
Composite materials are used in various industries such as marine, aircraft, automotive, etc. In marine applications, composites are exposed to seawater, which can affect their mechanical properties due to moisture absorption. This work focuses on the durability of composite materials under the short-term effect of seawater ageing. The specimens were prepared from glass fiber/epoxy using a hand lap-up method and stitched in the z-direction with Kevlar fiber. The specimens were submerged in seawater for 24 and 35 days. A significant decrease in maximum load was found as specimen immersion time in seawater increased. The seawater ageing also affected fracture toughness with a reduction of 30% for 24 days immersion and 55% for 35 days. The ageing also caused the swelling of composites due to moisture absorption, which increased the weight of the specimens. Compared to the dry specimens, the weight of the specimen for 24 days increases to 5.2% and 7.89% for 35 days’ seawater ageing. The analysis also showed that due to seawater ageing, the de-bonding rate increased as the number of days increased.

Temporal Analysis for Detection of Anomalies in Precipitation Patterns over a Selected Area in the Indus Basin of Pakistan - Akhtar Ali; Hafiz Umar Farid; Zahid Mehmood Khan; Ijaz Ahmad; Muhammad Naveed Anjum; Muhammad Mubeen; Aamir Shakoor (Pure and Applied Geophysics, 2021)

Research advances and applications of biosensing technology for the diagnosis of pathogens in sustainable agriculture - Qurban Ali; Sunny Ahmar; Muhammad Aamir Sohail; Muhammad Kamran; Mohsin Ali; Muhammad Hamzah Saleem; Muhammad Rizwan; Agha Mushtaque Ahmed; Freddy Mora-Poblete; Antônio Teixeira do Amaral Júnior; Mustansar Mubeen; Shafaqat Ali (Environmental Science and Pollution Research, 2021)

Lead availability and phytoextraction in the rhizosphere of Pelargonium species - Maria Manzoor; Iram Gul; Aamir Manzoor; Usman Rauf Kamboh; Kiran Hina; Jean Kallerhoff; Muhammad Arshad (Environmental Science and Pollution Research, 2020)

Comparative analysis of oil composition and antibacterial activity of aerial parts of Terminalia arjuna (Roxb.) - Shehar Bano; Azeem Intisar; Mahd Rauf; Abdul Ghaffar; Farhat Yasmeen; Waheed-Uz- Zaman; Uzma Intisar; Gulnaz Kausar; Nadeem Muhammad; Aqsa Aamir (Natural Product Research, 2020)

A forecasting model approach of sustainable electricity management by developing adaptive neuro-fuzzy inference system - Aamir Nawaz Khan; Muhammad Asif Nadeem; Muhammad Shahid Hussain; Muhammad Aslam; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2020)

Spicing up gastrointestinal health with dietary essential oils - Mahwish Tanveer; Charles Wagner; Muhammad Ikram ul Haq; Nilton C. Ribeiro; Thriumurugan Rathinasabapathy; Masood Sadiq Butt; Aamir Shehzad; Slavko Komarnytsky (Phytochemistry Reviews, 2020)

Characterization of a novel cotton MYB gene, GhMYB108-like responsive to abiotic stresses - Abid Ullah; Muhammad Tahir Ul Qamar; Mohammad Nisar; Ali Hazrat; Gul Rahim; Aamir Hamid Khan; Kashif Hayat; Saeed Ahmed; Waqar Ali; Aziz khan; Xiyan Yang (Molecular Biology Reports, 2020)

Temperature trends and elevation dependent warming during 1965–2014 in headwaters of Yangtze River, Qinghai Tibetan Plateau - Naveed Ahmed; Gen-xu Wang; Adeyeri Oluwafemi; Sarfraz Munir; Zhao-yong Hu; Aamir Shakoor; Muhammad Ali Imran (Journal of Mountain Science, 2020)

5-Endo-dig cyclizations in organic syntheses - Muhammad Aamir Sajid; Zulfiqar Ali Khan; Sohail Anjum Shahzad; Syed Ali Raza Naqvi; Muhammad Usman (Molecular Diversity, 2020)

First report of Nigrospora sphaerica causing leaf spot of date palm in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Shahbaz Ahmad; Mubeen Sarwar; Aamir Nawaz; Samiya Mahmood Khan; Sajid Ali; Sidra Aslam; Abdul Mannan (Journal of Plant Pathology, 2020)

Delineation of regional groundwater vulnerability using DRASTIC model for agricultural application in Pakistan - Aamir Shakoor; Zahid M. Khan; Hafiz U. Farid; Muhammad Sultan; Ijaz Ahmad; Naveed Ahmad; Muhammad H. Mahmood; Muhammad U. Ali (Arabian Journal of Geosciences, 2020)

Detection of antibodies to peste-des-petits-ruminants virus in the semi-domesticated yak - Muhammad Abubakar; Nosirjon Sattorov; Shumaila Manzoor; Ehtisham ul Haq Khan; Manzoor Hussain; Aamir Bin Zahur; Muhammad Afzal; Jonas Johansson Wensman (European Journal of Wildlife Research, 2019)
Peste des petits ruminants (PPR) is a highly contagious and acute viral disease of small ruminants. Occasionally, PPR can affect wildlife with devastating results, such as the recent outbreaks in Mongolian saiga. The yak ( Bos grunniens and Bos mutus ) is a large ruminant found throughout the Himalayan region of south Central Asia, the Tibetan Plateau and as far north as Mongolia and Russia. In Pakistan, yaks are confined to the high plateau of the Northern Areas, from Gilgit to the valley of Ladakh. In Tajikistan, yaks are present in districts in the north, east and southeast of the country. Commonly, yak intermingle with domestic animals during winter when mountainous summer pastures are covered with snow, and with wildlife during summer pastures. PPR is considered endemic in sheep and goats in Pakistan and Tajikistan. In this study, we investigated the potential presence of antibodies to peste-des-petits-ruminants virus (PPRV) in yak populations using ELISA. A total of 250 (Pakistan) and 85 (Tajikistan) serum samples of healthy yaks were collected. None of the Tajik yaks were seropositive (95% confidence interval (CI) 0.0–4.2%), while 23 of 250 (9.2%; 95% CI 5.9–13.5%) yaks sampled in Pakistan were found positive. Whether PPRV is continuously circulating among yaks or seroconversion reflects spill-over from outbreaks of PPR in domestic animals remains unknown. Due to the herding practices, yak might transmit PPR from domestic to wild ruminants. Differences in contacts between yaks and domestic animals in Pakistan and Tajikistan, or the low sample size, could explain that no Tajik yaks were seropositive.

Measuring the ecological footprint of inbound and outbound tourists: evidence from a panel of 35 countries - Muhammad Imran Qureshi; Elsayed Elsherbini Elashkar; Alaa Mohamd Shoukry; Alamzeb Aamir; Nik Hasnaa Nik Mahmood; Amran Md. Rasli; Khalid Zaman (Clean Technologies and Environmental Policy, 2019)

Dynamic linkages between tourism, energy, environment, and economic growth: evidence from top 10 tourism-induced countries - Kanwal Shaheen; Khalid Zaman; Rubeena Batool; Muhammad Adnan Khurshid; Alamzeb Aamir; Alaa Mohamd Shoukry; Mohamed A. Sharkawy; Fares Aldeek; Jameel Khader; Showkat Gani (Environmental Science and Pollution Research, 2019)

Economics of death and dying: a critical evaluation of environmental damages and healthcare reforms across the globe - Rubeena Batool; Khalid Zaman; Muhammad Adnan Khurshid; Salman Masood Sheikh; Alamzeb Aamir; Alaa Mohamd Shoukry; Mohamed A. Sharkawy; Fares Aldeek; Jameel Khader; Showkat Gani (Environmental Science and Pollution Research, 2019)

Comparative Analysis of Draft Genome Sequence of Rhodococcus sp. Eu-32 with Other Rhodococcus Species for Its Taxonomic Status and Sulfur Metabolism Potential - Nasrin Akhtar; Muhammad A. Ghauri; Kalsoom Akhtar; Sana Parveen; Muhammad Farooq; Aamir Ali; Peter Schierack (Current Microbiology, 2019)

Amelioration of toxicopathological effects of cadmium with silymarin and milk thistle in male Japanese quail (Coturnix japonica) - Muhammad Kashif Saleemi; Muhammad Waseem Tahir; Rao Zahid Abbas; Masood Akhtar; Aamir Ali; Muhammad Tariq Javed; Zahida Fatima; Muhammad Zubair; Sheraz Ahmed Bhatti; Zahoor Ul Hassan (Environmental Science and Pollution Research, 2019)

Prevalence and current therapy in chronic liver disorders - Muhammad Daniyal; Muhammad Akram; Rida Zainab; Naveed Munir; Aamir Sharif; Syed Muhammad Ali Shah; Bin Liu; Wei Wang (Inflammopharmacology, 2019)

Ni tolerance and its distinguished amelioration by chelating agents is reflected in root radius of B. napus cultivars - Humera Nawaz; Stephan Manhalter; Aamir Ali; Muhammad Yasin Ashraf; Ingeborg Lang (Protoplasma, 2019)

Multi-precursory Analysis of Phalla Earthquake (July 2015; Mw 5.1) Near Islamabad, Pakistan - Adnan Barkat; Aamir Ali; Khaista Rehman; Muhammad Awais; Muhammad Arslan Tariq; Junaid Ahmed; Muhammad Ayaz Amin; Talat Iqbal (Pure and Applied Geophysics, 2018)

Phytohormones enhanced drought tolerance in plants: a coping strategy - Abid Ullah; Hakim Manghwar; Muhammad Shaban; Aamir Hamid Khan; Adnan Akbar; Usman Ali; Ehsan Ali; Shah Fahad (Environmental Science and Pollution Research, 2018)

Rainfall–runoff, flood inundation and sensitivity analysis of the 2014 Pakistan flood in the Jhelum and Chenab river basin - Muhammad Junaid Siddiqui; Sajjad Haider; H.F. Gabriel; Aamir Shahzad (Hydrological Sciences Journal, 2018)

Development of a flood forecasting system using IFAS: a case study of scarcely gauged Jhelum and Chenab river basins - Aamir Shahzad; Hamza Farooq Gabriel; Sajjad Haider; Ammara Mubeen; Muhammad Junaid Siddiqui (Arabian Journal of Geosciences, 2018)

Prevalence of selected pharmaceuticals in surface water receiving untreated sewage in northwest Pakistan - Aisha Khan; Dilawar Farhan Shams; Waliullah Khan; Aamir Ijaz; Muhammad Qasim; Maryam Saad; Ayesha Hafeez; Shams Ali Baig; Nisar Ahmed (Environmental Monitoring and Assessment, 2018)

Alkali-Activated Boiler Fly Ash for Ni(II) Removal: Characterization and Parametric Study - Muhammad Samiullah; Zaheer Aslam; Adeem Ghaffar Rana; Aamir Abbas; Waqar Ahmad (Water, Air, & Soil Pollution, 2018)

Dietary exposure to HCH and DDT congeners and their associated cancer risk based on Pakistani food consumption - Muhammad Aamir; Sardar Khan; Gang Li (Environmental Science and Pollution Research, 2018)

A measles outbreak in Sindh, Pakistan caused by a genotype B3 virus - Syed Sohail Zahoor Zaidi; Abdul Hameed; Naeem Ali; Massab Umair; Muhammad Masroor Alam; Muhammad Suleman Rana; Salmaan Sharif; Uzma Bashir Aamir; Shahzad Shaukat; Mehar Angez; Adnan Khurshid; Ribqa Akhtar; et al. (Archives of Virology, 2017)

Occurrence, enantiomeric signature and ecotoxicological risk assessment of HCH isomers and DDT metabolites in the sediments of Kabul River, Pakistan - Muhammad Aamir; Sardar Khan; Lili Niu; Siyu Zhu; Anwarzeb Khan (Environmental Geochemistry and Health, 2017)

Congener-specific evaluation of biota-sediment accumulation factor model for HCHs and DDTs under small-scale in situ riverine condition - Muhammad Aamir; Sardar Khan; Mengling Tang; Zahir Qamar; Anwarzeb Khan; Javed Nawab (Journal of Soils and Sediments, 2017)

Rock physics modelling in reservoirs within the context of time lapse seismic using well log data - Muhammad Toqeer; Aamir Ali (Geosciences Journal, 2017)

Effect of Shale Distribution on Hydrocarbon Sands Integrated with Anisotropic Rock Physics for AVA Modelling: A Case Study - Aamir Ali; Zubair; Matloob Hussain; Khaista Rehman; Muhammad Toqeer (Acta Geophysica, 2016)

Health risk assessment from contaminated foodstuffs: a field study in chromite mining-affected areas northern Pakistan - Javed Nawab; Gang Li; Sardar Khan; Hassan Sher; Muhammad Aamir; Isha Shamshad; Anwarzeb Khan; Muhammad Amjad Khan (Environmental Science and Pollution Research, 2016)

Gaseous pollutants from brick kiln industry decreased the growth, photosynthesis, and yield of wheat (Triticum aestivum L.) - Muhammad Adrees; Muhammad Ibrahim; Aamir Mehmood Shah; Farhat Abbas; Farhan Saleem; Muhammad Rizwan; Saadia Hina; Fariha Jabeen; Shafaqat Ali (Environmental Monitoring and Assessment, 2016)

A Novel Approach Based on Data Redundancy for Feature Extraction of EEG Signals - Hafeez Ullah Amin; Aamir Saeed Malik; Nidal Kamel; Muhammad Hussain (Brain Topography, 2016)

Organic amendments impact the availability of heavy metal(loid)s in mine-impacted soil and their phytoremediation by Penisitum americanum and Sorghum bicolor - Javed Nawab; Sardar Khan; Muhammad Aamir; Isha Shamshad; Zahir Qamar; Islamud Din; Qing Huang (Environmental Science and Pollution Research, 2016)

Geotechnical study of marble, schist, and granite as dimension stone: a case study from parts of Lesser Himalaya, Neelum Valley Area, Azad Kashmir, Pakistan - Sohail Mustafa; Muhammad Arshad Khan; Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Aamir Asghar; Abrar Niaz (Bulletin of Engineering Geology and the Environment, 2015)

Spatio-temporal variations of b-value in and around north Pakistan - Khaista Rehman; Asghar Ali; Sajjad Ahmed; Wajid Ali; Aamir Ali; Muhammad Younis Khan (Journal of Earth System Science, 2015)

NutriTRAILomics in prostate cancer: time to have two strings to one’s bow - Ammad Ahmad Farooqi; Aamir Rana; Asma M. Riaz; Ammara Khan; Muhammad Ali; Sara Javed; Shahzeray Mukhtar; Sehrish Minhaj; Javeria Rafique Rao; Javairia Rajpoot; Rafia Amber; Fiza Asif Javed; et al. (Molecular Biology Reports, 2012)

Production and Stability Evaluation of Modified-Release Microparticles for the Delivery of Drug Combinations - Muhammad Naeem Aamir; Mahmood Ahmad (AAPS PharmSciTech, 2010)